Dark Triad Personality and Infidelity Intention: A Study on Individuals in Long-Distance Marriage - Sari, Riska Indah; Ratnasari, Yudiana (Psikostudia : Jurnal Psikologi, 2026)
Individuals who live in a long-distance marriage have a greater challenge to maintain their relationship, one of them in terms of loyalty to their partner. This study is a cross-sectional quantitative study that aims to see whether the dark triad personality and relationship quality affect the infidelity intention. Sampling of participants using purposive sampling and collected research participants amounted to 310people aged 21-59 who are married and are undergoing a long-distance marriage with a minimum distance of 80 Km. The results of the multiple linear regression analysis, controlling for gender, indicate that within the dark triad personality dimensions, machiavellianism has a significant negative effect on infidelity intention, while psychopathy has a significant positive effect. However, narcissism does not significantly predict infidelity intention. Furthermore, the comparative analysis reveals a significant gender difference in infidelity intention, with males exhibiting higher levels than females. These findings suggest that infidelity intention is driven by impulsivity, weak self-control, and a focus on short-term gratification. Conversely, high self-control, deliberate planning, and a long-term orientation appear to diminish such intentions